Artificial Intelligence in Electronic Commerce: Basic Chatbots and Consumer Journey - Eliza Nichifor; Adrian Trifan; Elena Mihaela Nechifor (Amfiteatru Economic)
This study aims to empirically cover the impact of the use of artificial intelligence through chatbots on online retail in terms of content implemented in the communication process. The presented research brings a contribution to the specialized literature by analyzing the perceived utility and demonstrating the facility, key concepts of the Technology Acceptance Model. In this sense, ten online stores in Romania were studied, selected according to the number of users, the research being carried out through a non-reactive method - content analysis. The method of data collection was that of the “mysterious client” in order not to generate a change in the behavior of the entities studied. The interpretation of the data obtained through the content grid allowed a horizontal and vertical approach that led to a series of results that confirmed the low level of performance of market leaders, as well as the high potential of this type of technology applied in the field. Regarding the impact of the use of chatbots, it has been shown that poor quality of the content displayed to users affects the consumer's journey, the point of satisfaction not being reached in these conditions